Pembinaan Madrasah Jalur Formal di Pesantren (Telaah Implementasi UU Nomor 18 Tahun 2019) - Mustofa, Idam; Raikhan (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
Law Number 18 of 2019 provides the legal basis for integrating madrasahs with Islamic boarding schools (pesantren), aiming to ensure that formal madrasahs within pesantren meet national education standards. One of the challenges faced by formal madrasahs in pesantren is meeting the standards of formal education, including facilities, teacher qualifications, and appropriate curriculum. This research aims to broaden understanding and contribute to the development of formal madrasahs within pesantren. In this study, the researcher employed a secondary data analysis method following the procedures formulated by Heaton from Andrews. The research findings indicate that the development of formal madrasahs within pesantren demonstrates that pesantren are not solely focused on religious education but also provide opportunities for students to receive quality formal education. Several efforts can be made to address the challenges of formal madrasahs within pesantren, including enhancing the quality of education, teacher training to improve qualifications, collaboration with higher education institutions, improving facilities and infrastructure, developing integrated curricula, providing guidance and mentoring, establishing collaborative networks, and strengthening funding. As an alternative solution, it is recommended to transform the top-down and discriminatory approach to madrasah development into a participatory approach in order to achieve effectiveness. The development of formal madrasahs within pesantren towards effective madrasahs can refer to well-established madrasah development programs that have proven their credibility as models.